PENINGKATAN AKTIVITAS PEMBELAJARAN DENGAN METODE TALKING STICK DI KELAS V SD NEGERI 27 PONTIANAK - Yuanita, Asih; Marzuki, Marzuki; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract: The aims of this research to describe talking stick to improve the learning activities of Social Sciences Kelas V SD Negeri 27 Pontianak Tenggara. The research method is descriptive, the form of research is Classroom Action Research is collaborative. The research data collection technique is direct observation. Research collection tools in the form of observation sheets. This research was conducted for three cycles. The results of this study include: The ability of teachers to plan talking stick learning in cycles I, II, and III with an average value of 3.78 (good category). The ability of teachers to carry out learning in cycles I, II, and III with an average value of 3.81 (good category). Physical activity with an average value of 33.33% increased with an average value of 88.17% (cycles I, II, III). Mental activity of 18.33% rose to an average value of 59.02%. Emotional activity from 26.67% increased to 67.21%. Based on data analysis of students 'learning activities, it shows that learning with Talking Sticks can improve students' learning activities. Keywords: Learning Activities, Talking Sticks, and Social Sciences